KUASA DAN KEKERASAN : KELEMBAGAAN PREMANISME YOGYAKARTA PASKA REFORMASI - Raharjo Jati, Wasisto (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2012)
After â€œReformasiâ€, the state lost his governability that implicate frozen democracy. Frozen democracy represent the terms which snugly to depict the resignment of state in social politics arena in society so that creater vacuum of power nowadays. This opportunity later then generate to attend the non state actors to exploit thatâ€™s for the sake of person and also groups. For the reason later then happen contestation in reaching for the power by using violence as instrument. As for this violence is happened by as existing state deligimation to making prosperity function so that generate the informal power in society especially urban society. â€œPremanâ€ as informal violence actor realize vacuum of power in society with forming organizational assorted. By defining democratize their own version, â€œpremanâ€ tried to run the prosperity function among them in violence logic with their repressive and intimidation act. Therefore by adopting the seminal concept of structural - violence in the Johan Galtungâ€™ violence theory, this paper endeavors to analyse the violence logic in informal power conducted by â€œpremanâ€ in dynamics of urban society. Kata kunci : Preman, Premanisme, Kekerasan, dan Kekuasaan.